2020
DOI: 10.1007/s40620-020-00805-1
|View full text |Cite
|
Sign up to set email alerts
|

Digital pathology for the routine diagnosis of renal diseases: a standard model

Abstract: Whole-slide imaging and virtual microscopy are useful tools implemented in the routine pathology workflow in the last 10 years, allowing primary diagnosis or second-opinions (telepathology) and demonstrating a substantial role in multidisciplinary meetings and education. The regulatory approval of this technology led to the progressive digitalization of routine pathological practice. Previous experiences on renal biopsies stressed the need to create integrate networks to share cases for diagnostic and research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Although our findings support the claim that SE-SEM evaluation is a powerful tool for analysing renal biopsies, the crucial role that TEM plays in diagnostic renal pathology is undisputed [27][28][29], and there is no doubt that SE-SEM does not achieve the resolution power of TEM. However, SE-SEM is a valuable alternative to TEM when high-resolution imaging of a large volume of the sample is needed or when the pathologist does not need (A-C) the identification of the glomerulus using light microscopy on toluidine blue stained 1 µm sections and then (D) the collection of 100 nm sections on copper TEM grids for (E-G) observation with TEM; (H-K) SE-SEM method protocol, including (H) collection of 1 µm sections on carboncoated slice and (I-K) observation by an ultra-high-resolution field-emission SEM of the semi-thin (1 µm) section.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Although our findings support the claim that SE-SEM evaluation is a powerful tool for analysing renal biopsies, the crucial role that TEM plays in diagnostic renal pathology is undisputed [27][28][29], and there is no doubt that SE-SEM does not achieve the resolution power of TEM. However, SE-SEM is a valuable alternative to TEM when high-resolution imaging of a large volume of the sample is needed or when the pathologist does not need (A-C) the identification of the glomerulus using light microscopy on toluidine blue stained 1 µm sections and then (D) the collection of 100 nm sections on copper TEM grids for (E-G) observation with TEM; (H-K) SE-SEM method protocol, including (H) collection of 1 µm sections on carboncoated slice and (I-K) observation by an ultra-high-resolution field-emission SEM of the semi-thin (1 µm) section.…”
Section: Discussionsupporting
confidence: 58%
“…Although our findings support the claim that SE-SEM evaluation is a powerful tool for analysing renal biopsies, the crucial role that TEM plays in diagnostic renal pathology is undisputed [27][28][29], and there is no doubt that SE-SEM does not achieve the resolution power of TEM. However, SE-SEM is a valuable alternative to TEM when high-resolution imaging of a large volume of the sample is needed or when the pathologist does not need to reach maximum magnifications for the purposes of the study.…”
Section: Discussionsupporting
confidence: 58%
“…Finally, the adoption of computer-aided diagnostic and artificial-intelligence tools is allowing the construction of a digital hub based in Caltagirone ("House of the Science") that will coordinate the widest renal pathology network in Italy, collecting cases from an already established nephropathology service in the North of the country that migrated all the routine renal biopsy diagnoses to WSI in 2014 [32]. This will further guarantee an equal access to the best diagnostic renal pathology services without the need to move patients, glass slides or paraffin blocks around Italy, additionally constructing a reposi-tory of non-neoplastic renal diseases that can serve as an educational atlas as well as a research database.…”
Section: Discussionmentioning
confidence: 99%
“…Digital pathology was used only for educational or consulting purposes until their regulatory approval for clinical employment in routine pathological practice ( L’Imperio et al, 2020 ). In studies in the United States and Europe, the regulatory approval of digital pathology research results has been reported, and the similarity of WSI diagnosis to the pathological diagnosis (using a conventional microscope) has been confirmed ( L’Imperio et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%